Bank asset quality and monetary policy pass-through - David Byrne; Robert Kelly (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2019)
The funding mix of European firms is weighted heavily towards bank credit, which underscores the importance of efficient pass-through of monetary policy actions to lending rates faced by firms. Euro area pass-through has shifted from being relatively homogenous to being fragmented and incomplete since the financial crisis. Distressed loan books are a crisis hangover with direct implications for profitability, hampering banks ability to supply credit and lower loan pricing in response to reductions in the policy rate. This paper presents a parsimonious model to decompose the cost of lending and highlight the role of asset quality in diminishing pass-through. Using bank-level data over the period 2008-2014, we empirically test the implications of the model. We show that a one percentage point increase in the impairment ratio lowering short run pass-through by 3 percent. We find that banks with severely impaired balance sheets do not adjust their loan pricing in response to changes in the policy rate at all. We derive a measure of the hidden bad loan problem, the NPL gap, which we define as the excess of non-performing loans over impaired loans. We show that it played a significant role in the fragmentation of euro area pass-through post-crisis.
Keywords: D43; E51; E52; E58; G21; 330; Monetary Policy Pass-through; Impaired Loans; Non-Performing Loans; Interest Rates